Mastiff - Pierce, Tamora (Pierce, Tamora. Beka Cooper, 2018)
Beka, having just lost her fiance in a slaver's raid, is able to distract herself by going with her team on an important hunt at the queen's request, unaware that the throne of Tortall depends on their success.